Land Procurement for Upstream Oil and Gas Business Activities in Indonesia - Subadi, Subadi (Brawijaya Law Journal : Journal of Legal Studies, 2021)
This paper aims to provide an understanding and insight regarding land procurement for oil and gas exploration activities as well as the development of regulations or legal and policy breakthroughs that have so far not been or very little exposed. Land procurement has always been a serious obstacle or obstacle to oil and gas exploration activities in Indonesia. Land procurement for oil and gas exploration using a business to business (B to B) mechanism makes it very difficult for SKK Migas and the contractor. In recent years, the government has made legal breakthroughs to simplify and accelerate the land procurement mechanism for exploration activities. This study uses a normative juridical method supported by in-depth interviews with legal experts, land acquisition committees and landowners and has produced conclusions: First, the business to business (B to B) mechanism often faces obstacles and obstacles, such as; 1) refusal from the landowner; 2) inconsistency with the spatial layout; 3) there is a land dispute with other parties; 4) it is difficult for oil and gas contractors to process land certification. Second, the discretion which is considered as a legal breakthrough or new policy that is ideal in helping to smooth and accelerate the process of oil and gas production in Indonesia.